2009
DOI: 10.1111/j.1365-2184.2009.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of Nucleostemin suppression on cell cycle arrest and apoptosis in the bladder cancer cell lines 5637 and SW1710

Abstract: Our data indicate that NS expression is necessary for cell proliferation and evasion of apoptosis in bladder cancer cells, independent of its effect on p53. Also, we speculate that the precise effect of NS on cell cycle regulation may relate to functional status of RB1 and CDKN2A/p16(INK4A).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Studies that reported a G1/S arrest phenotype following nucleostemin-knockdown include those performed in U2OS cells (Dai et al, 2008;Ma and Pederson, 2007), SW1710 cells (Nikpour et al, 2009), HeLa cells (Sijin et al, 2004), PC-3 cells (Liu et al, 2010) and bone marrow-derived stromal stem cells (Jafarnejad et al, 2008). In contrast, the finding that nucleostemin-depleted cells are arrested at the G2/M phase has also been reported in several studies performed in U2OS cells (Meng et al, 2008), HeLa cells (Romanova et al, 2009), 5637 cells (Nikpour et al, 2009) and mouse embryonic fibroblast cells (MEFs) (Zhu et al, 2006). It is noted that the studies describing G1/S arrest used cells with either wild-type or mutant forms of p53, retinoblastoma, p16 and alternate reading frame (p14ARF) protein (both encoded by CDKN2A), and studies describing G2/M arrest also used cells with wild-type or mutant forms of p53, retinoblastoma, p16 and p14ARF.…”
Section: The Amazing Diversity Of Cell-cycle-arrest Profiles Of Nuclementioning
confidence: 99%
“…Studies that reported a G1/S arrest phenotype following nucleostemin-knockdown include those performed in U2OS cells (Dai et al, 2008;Ma and Pederson, 2007), SW1710 cells (Nikpour et al, 2009), HeLa cells (Sijin et al, 2004), PC-3 cells (Liu et al, 2010) and bone marrow-derived stromal stem cells (Jafarnejad et al, 2008). In contrast, the finding that nucleostemin-depleted cells are arrested at the G2/M phase has also been reported in several studies performed in U2OS cells (Meng et al, 2008), HeLa cells (Romanova et al, 2009), 5637 cells (Nikpour et al, 2009) and mouse embryonic fibroblast cells (MEFs) (Zhu et al, 2006). It is noted that the studies describing G1/S arrest used cells with either wild-type or mutant forms of p53, retinoblastoma, p16 and alternate reading frame (p14ARF) protein (both encoded by CDKN2A), and studies describing G2/M arrest also used cells with wild-type or mutant forms of p53, retinoblastoma, p16 and p14ARF.…”
Section: The Amazing Diversity Of Cell-cycle-arrest Profiles Of Nuclementioning
confidence: 99%
“…Furthermore, Nikpour et al [19] were found over-expression of nucleostemin in the most uroepithelial carcinoma cell lines. They suggest involvement of nucleostemin differs even between tumors of the same type, like invasive bladder cancers.…”
Section: Discussionmentioning
confidence: 97%
“…Effects shown include a G1/S arrest (Dai et al, 2008;Ma and Pederson, 2007;Nikpour et al, 2009) 2009; Romanova et al, 2009a;Zhu et al, 2006). This discrepancy cannot be explained by the status of p53, Rb or p16 in the cell models used.…”
Section: The Effect Of Nucleostemin Depletion On Cell-cycle Progressionmentioning
confidence: 92%